Daya Beda, Tingkat Kesulitan, dan Tebaan Tes Biologi Kelas 8 Semester Gasal - Suwarto Suwarto (Universitas Sebelas Maret, 2016)
The aims of this research: (1) Want to know different effort in biology test items at 8 class odd semester, (2) want to know difficult level in biology test items at 8 class odd semester, (3) want to know guessing biology test items at 8 class odd semester. Biology test 8 class odd semester includes 100 question items and have tried on 200 respondent. For analysis is used R programming. The results show: (1) Different effort in biology test items at 8 class odd semester about 1,002 up to 2,969. The lowest different effort item is 8 item and the highest different effort item is 38 item. (2) Difficult level in biology test items at 8 class odd semester about 1,005 un to 1,992. The lowest difficult level test item is 83 and 93 item and the highest difficult level is 45 item. (3) Guessing biology test items at 8 class odd semester. Biology test 8 class odd semester about 0,018 up to 0,989. The lowest guessing is 80 item and the highest guessing is 68 item.Keywords: Discrimination, Difficulty, and Guessing